2023
DOI: 10.3389/fimmu.2023.1230718
|View full text |Cite
|
Sign up to set email alerts
|

Non-classical HLA-E restricted CMV 15-mer peptides are recognized by adaptive NK cells and induce memory responses

Nerea Martín Almazán,
Benedetta Maria Sala,
Tatyana Sandalova
et al.

Abstract: IntroductionHuman cytomegalovirus (HCMV) reactivation causes complications in immunocompromised patients after hematopoietic stem cell transplantation (HSCT), significantly increasing morbidity and mortality. Adaptive Natural Killer (aNK) cells undergo a persistent reconfiguration in response to HCMV reactivation; however, the exact role of aNK cell memory in HCMV surveillance remains elusive.MethodsWe employed mass spectrometry and computational prediction approaches to identify HLA-E-restricted HCMV peptides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 69 publications
2
2
0
Order By: Relevance
“…Our hypothesis suggests that these molecules play a pivotal role in discerning between self and nonself-peptides. On the other hand, we found that HLA-E and NKG2C are important for the recall responses in aNK cells, which has been earlier reported by us and others in defense against viruses (12,47). Moreover, we found e.g., a greater TNFα secretion by aNK cells following a secondary stimulation with specific tumor cells, which facilitates the activation of the transcription factor AP-1 that is activated both in antigen specific T cells and clonal expanded NK cells (46,48).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Our hypothesis suggests that these molecules play a pivotal role in discerning between self and nonself-peptides. On the other hand, we found that HLA-E and NKG2C are important for the recall responses in aNK cells, which has been earlier reported by us and others in defense against viruses (12,47). Moreover, we found e.g., a greater TNFα secretion by aNK cells following a secondary stimulation with specific tumor cells, which facilitates the activation of the transcription factor AP-1 that is activated both in antigen specific T cells and clonal expanded NK cells (46,48).…”
Section: Discussionsupporting
confidence: 87%
“…However, the interaction of cDC1 was more restricted to aNK cell (Figure 2E). Exploring the top ligand-receptor underlying cDC1-aNK cell interaction, identified HLA-E-KLRC2 which may play a role in antigen presentation as was demonstrated in our previous study (12). Other significant interactions were revealed including CXCL1-CXCR2, HLA-C-KIR2DL3, CLEC2B-KLRF1, which are involved in chemotaxis, NK cell education, and antigen presentation and cytotoxicity, respectively.…”
Section: Ank Cell Genetic Signature In Ovarian Cancer Patients Reveal...supporting
confidence: 57%
See 2 more Smart Citations